Evaluation of Prevalence and Characteristics of Patients with Fanconi Anemia: A Study in Northeast of Iran - Sepideh Shakeri; Narjes Soltani; Mohammad Reza Javan; mehrnaz abdolalian; Hossein Ayatollahi; fatemeh shams (Medical Laboratory Journal, 2023)
Background and objectives: Fanconi anemia (FA) is an autosomal recessive disorder that usually manifest in forms of pancytopenia, hyperpigmentation, and skeletal complications. Mutation in the DNA repair regulatory genes is associated with the development of FA. Examination of chromosomal breakages when chromosomes are exposed to cross-linking agents is a common method of FA diagnosis. This study aimed to evaluate the prevalence and characteristics of patients with FA in Mashhad, northeast of Iran. Methods: In this study, we evaluated 312 suspected FA patients who had been referred to the laboratory of Ghaem Hospital during 2014-2020. The mitomycin C method was used to identify FA-positive subjects. Results: After the examinations, 84 patients (26.9%) were cytogenetically positive for FA. Of 84 patients, 48 (57.1%) were male and 36 (42.9%) were female. Thumb abnormality was the most common congenital anomaly (43.2%). Conclusion: Based on the findings, males are more susceptible to FA, and thumb abnormality is the most common congenital anomaly associated with FA. Combination of clinical manifestations and genetic susceptibility in patients may contribute to a more accurate diagnosis.